Local impacts of a global crisis: Food price transmission and poverty impacts in Ghana - Cudjoe, Godsway; Breisinger, Clemens; Diao, Xinshen (International Food Policy Research Institute, 2008)
Recent increases in cereals prices raise questions about agricultural priorities in Ghana. This report presents an application of the Policy Analysis Matrix (PAM) to the problem of identifying opportunities to enhance agriculture’s contribution to economic growth and poverty alleviation in the country. The PAM is a budget-based method that was applied to study the social and private profitability of six maize production systems and six rice production systems. The results indicate that all twelve of the systems contribute to national economic growth and private income generation among farmers, at least under the high cereals prices that prevailed in 2007. Maize systems show a higher rate of return (lower cost/benefit ratio) than rice systems. If prices returned to lower levels experienced in 2005, however, rice systems would be privately and socially unprofitable. Return to the still lower prices of 2002 would leave both the maize and rice systems unprofitable. The PAM was also used to assess the impact of alternative interventions for increasing profitability in the face of lower output prices. The results suggest that higher adoption of input technologies could make maize profitable under a very wide range of prices. However, fertilizer prices are not likely to be the constraining factor input adoption as the price of fertilizer has little impact on farm profitability given current levels of fertilizer use. Rather, further research is needed to determine how to promote improved maize production technology. For rice systems there appears to be room to enhance profitability through post-farm interventions to reduce processing losses and to improve the quality of locally grown rice. Rice systems would be profitable under very low output prices if Ghana achieved the processing conversion rates and milled rice quality found in other countries.